Formation of identity through the lens of psychogeography in selected Chan Ling Yap’s novels - Amran, Nurul Atiqah (2022)
Identity is the prevalent topic in Malaysian Literature in English, but it is rarely discussed from the psychogeography lens. Past studies tend to approach Malaysian diasporic texts from the postcolonial theory and mainly focus on memory and trauma. Thus far, the discussions on Chan Ling Yap’s works are limited to constructing multicultural space and identity. Therefore, my thesis attempts to delve into the urban realms and identity of the city inhabitants in four selected Chan Ling Yap’s novels: Sweet Offerings (2009), Bitter-Sweet Harvest (2011), New Beginnings (2014) and A Flash of Water (2016). I employ the theory of psychogeography by giving specific attention to its evolving branches, literary psychogeography, to study how urban settings affect the characters’ emotions and behaviours in literature. The objectives are; to investigate aspects that influence the characters’ movements and engagements with the urban environment, to examine the psychological process between the characters and the urban environment, and to analyse the representations and portrayals of the urban environment in Yap’s selected works that influence characters’ identity formation. The analysis chapter is divided into two steps. The first step identifies the main characters in the novels on their active movement and close connection to the urban realms. The second step is the textual analysis based on a threetiered model, each with a distinct variable focusing on gender, psychology and urban studies. The characters’ movements are examined using three thematic concerns inspired by Bridger’s and Harlow’s spatiality, temporality and embodiment. It further explores the psychology of the human senses, drawing from the sensual theory of modernity. The third tier of the analysis approaches the geographical part that draws from Lehan’s, Lynch’s and William’s theory of the city in literature by emphasising the urban portrayals and perceptions. The theory develops our conscious awareness of how the urban environment feeds our emotions and drives us to change and make changes and to empower and be empowered. My thesis shows that the female characters claim their position in the city by breaking the boundaries of the masculine construction in the urban vicinity. The male characters partially embody the contemporary Western model of an urban dweller. They possess some flâneur traits but are distinctly unique in that they enter and exit their urban spheres for various reasons. The local literary texts analysed and used in the psychogeography discussion thus far were mainly focused on the collection of poems produced by our local poets and novels written by Malaysian diasporic writers. Further research may compare the existing texts with other relevant texts from different genres or establish a new study for a more current text that portrays the present condition of our local metropolis.